A look at electric bike casualties: Do they differ from the mechanical bicycle?. (December 2018) - ,; Bahouth, H.; Becker, A.; Jeroukhimov, I.; Karawani, I.; Kessel, B.; Klein, Y.; Lin, G.; Merin, O.; Bala, M.; Mnouskin, Y.; Rivkind, A.; et al.
Abstract: Objective: To evaluate and compare, at the national level, injury trends and, characteristics and to identify high risk groups of electric bike (E-bike) and mechanical bicycle (M-bike) related hospitalizations as a key message for public policy. Methods: Historic prospective study based on data from the Israel National Trauma Registry (INTR), between 1.1.2013 and 31.12.2017. All hospitalized casualties were E-bikers and M-bikers. Results: During the study period, 1733 E-bikers and 7259 M-bikers were hospitalized. Arab children (age 0–15) and young adults (age 16–29) were at higher risk for E-bike and M-bike casualties respectively. The hospitalization rate per 1000 vehicles was lower for E-bikers in comparison to M-biker. However, during the five year period a dramatic increase in E-bike related hospitalizations was reported coinciding with a decrease of M-bike related casualties. Among M-bikers, the decrease in hospitalization rate was for accidents on both inter and intra-city roads, but not on unpaved roads, which remained stationary, suggesting that the transportation mode is changing. In comparison to the M-bikers, E-bikers were at greater risk for enduring head injuries (OR 1.16 95% CI 1.00–1.25) and lower extremity injuries (OR 1.37 95% CI 1.23–1.52), to undergone surgery (OR 1.13 95% CI 1.00–1.26), having longer hospital stays (OR 1.44 95% CI 1.23–1.68) and being discharged to rehabilitation center (OR 1.43 95% CI 1.09–1.86). Conclusion: During the last five years in Israel there is a dramatic increase in E-bike related hospitalized casualties corresponding to a substantial increase in E-bike usage. In comparison to M-bikers, there is a lower casualty rate but these casualties are more severely injured and utilize more hospital resources. It is of utmost importance to identify these high risk groups in an effort to develop culturally appropriate interventions for these road users, including training, awareness and helmet enforcement. Policy change recommendations are discussed. Highlights: There is an increase in E-bike related casualties especially on inter / intra city. E-bike seems to replace the M- bike as a transportation mode. E-bikers have a higher risk for head injury compared to cyclists. The ability to benefit from the use of E-bike relies on a series of regulations, enforcement, training and education of these road users.